The Impact of Incident-Based Learning on Network Security Practicum: Effects on Analytical and Response Skills - A. Sri Bungsu Asma; Ahmad Syawaluddin; Muflihah Qanita H; Muh. Yasyfin Farhan; Muh.Kidfari; Muhammad Arsyad Meru; Muhammad Fadli Kasman (Information Technology Education Journal, 2025)
The purpose of this study is to examine the effectiveness of Incident-Based Learning (IBL) in improving students' analytical and incident response skills within network security practicum courses. The research addresses the gap in existing cybersecurity education by testing the impact of IBL compared to conventional practicum approaches, with the aim to better prepare students for dynamic and unstructured cybersecurity threats. This study employed a true experimental design with a pretest–posttest control group format. Two groups of undergraduate students participated in the study: one exposed to Incident-Based Learning and the other following a conventional practicum approach. Data were collected using performance-based assessments that measured analytical skills and incident response abilities, followed by statistical analysis using paired and independent samples t-tests, and MANOVA. The results revealed that students in the IBL group showed significantly higher improvements in both analytical skills (t(58) = 2.94, p < 0.01) and incident response skills (t(58) = 3.20, p < 0.01) compared to the control group. The MANOVA confirmed a significant multivariate effect (p < 0.05) of IBL on both competencies. While the findings suggest that IBL enhances practical cybersecurity competencies, the study's limitations include its sample size and scope, which may impact the generalizability of results to broader educational contexts. This study contributes to the field by providing empirical evidence on the effectiveness of IBL in cybersecurity education. It offers a valuable framework for improving network security curricula and paves the way for future research on integrating IBL into various technical education domains